Metode Kokristal, Koamorf, Kompleks Inklusi, dan Dispersi Padat dalam Upaya Modifikasi Sifat Fisikokimia Zat Aktif Farmasi - Nadya Azzahra; Fitrianti Darusman; Aulia Fikri Hidayat (UNISBA Press, 2024)
Abstract. Modification of the physicochemical properties of active pharmaceutical ingredients is an important step in enhancing the solubility and bioavailability of drugs. Several modifications that can be implemented include cocrystals, coamorphous systems, inclusion complexes, and solid dispersions. Cocrystals involve the formation of new crystals with the active ingredient and a coformer, which can improve solubility and stability. Coamorphous systems are amorphous systems that utilize a mixture of the active ingredient with a coformer to enhance solubility. Inclusion complexes use host molecules like cyclodextrins to encapsulate the active ingredient, thereby increasing its stability and solubility. Solid dispersions involve the distribution of the active ingredient in a polymer matrix to enhance solubility and dissolution rate. These modifications of the physicochemical properties of active pharmaceutical ingredients will improve the solubility and bioavailability of drugs in the body. Abstrak. Modifikasi sifat fisikokimia zat aktif farmasi merupakan langkah penting dalam meningkatkan kelarutan dan bioavalabilitas obat. Beberapa modifikasi sifat fisikokimia yang dapat dilakukan adalah kokristal, koamorf, kompleks inklusi, dan dispersi padat. Kokristal melibatkan pembentukan kristal baru dengan zat aktif dan koformer yang dapat meningkatkan kelarutan dan stabilitas. Koamorf adalah sistem amorf yang memanfaatkan campuran zat aktif dengan koformer untuk memperbaiki kelarutan. Kompleks inklusi menggunakan molekul host seperti siklodekstrin untuk mengenkapsulasi zat aktif, meningkatkan stabilitas dan solubilitasnya. Dispersi padat melibatkan distribusi zat aktif dalam matriks polimer untuk meningkatkan kelarutan dan laju disolusi. Modifikasi sifat fisikokimia zat aktif farmasi ini akan meningkatkan kelarutan dan bioavalabilitas obat di dalam tubuh.